1990
DOI: 10.1159/000168069
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Red Cell Size: Diagnostic Value and Determinants

Abstract: Urinary red blood cells (RBC) are usually small and morphologically abnormal in glomerular (GN) hematuria, and slightly enlarged and morphologically normal in nonglomerular (NG) hematuria. This study was performed to evaluate the diagnostic value of urinary red cell size and morphology and to investigate the mechanism of the alteration in cell size. In 34 consecutive patients with hematuria we examined the urinary RBC size distribution and mean corpuscular volume (MCV) by electronic sizing of suspensions of RB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
1

Year Published

1991
1991
2012
2012

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 24 publications
1
4
1
Order By: Relevance
“…The model was more effective when the stresses were applied simultaneously than when applied sequentially, although the latter more closely simulates in vivo conditions. Their conclusion is in accord with our recent conclusion, based on studying urinary MCV dur ing a furosemide-induced diuresis, that both glomerular and tubular injuries to red cells are necessary to explain the full degree of microcytosis of glomerular hematuria [10].…”
Section: Dear Sirsupporting
confidence: 90%
See 2 more Smart Citations
“…The model was more effective when the stresses were applied simultaneously than when applied sequentially, although the latter more closely simulates in vivo conditions. Their conclusion is in accord with our recent conclusion, based on studying urinary MCV dur ing a furosemide-induced diuresis, that both glomerular and tubular injuries to red cells are necessary to explain the full degree of microcytosis of glomerular hematuria [10].…”
Section: Dear Sirsupporting
confidence: 90%
“…We also believe that hemolysis of a subset of nonglom erular red cells, due to a combination of hypotonicity and acidity, probably accounts for the 'mixed' red cell size histogram patern that has been observed by us and others in nonglomerular hematuria [10][11][12][13]. It would be interest ing to reanalyze the hemolysis data of Turitzen et al [1] in light of the interaction between tonicity and pH.…”
Section: Dear Sirmentioning
confidence: 67%
See 1 more Smart Citation
“…Studies using this criteria have reported sensitivities and specificities ranging from 52% to 100% and 98% to 100%, respectively [3,4,8,20,26].…”
Section: Discussionmentioning
confidence: 99%
“…These might not be identical in all patients with glomerulonephritis. Recent research on the mechanisms of erythrocyte dysmorphism suggests that mechanical damage caused by passage through the glomerular membrane [14,26,29], osmotic stress during the passage through the hypotonic renal tubular segment [26,30], urine pH [30,31], and ion concentration [32] might be important in determining the shape of the urinary red cell. Kohler et al [3] and Tomita et al [4] were unable to confirm the effect of urine pH and osmolality on red cell morphology.…”
Section: Discussionmentioning
confidence: 99%